Gênesis bíblico versus Teogonia(s): o mito da criação e a relação criador e criatura - Bastos, Jacqueline Silva (2021)
The present aims basically to compare narratives: the Biblical Genesis, the Theogony of Hesiod and other similar narratives. Thus, we aim to analyze the relationship between creator and creature more often and specifically in two cultures: Judeo-Christian and Greek. The guiding thread of our study is the need that both of these cultures have to present and affirm a greater God, sovereign over everything and everyone. The biggest difference, perhaps, lies in the fact that Greek culture coexists with several gods and affirms Zeus as the god of gods and men, in a hierarchical polytheism, explained in the Theogony of Hesiod and expanded from the myths in this work mentioned in other works. mythological narratives and poems, while Judeo- Christian culture, represented primarily by the Hebrew people, reveals a unique God, Creator of everything and everyone, the center of a monotheistic culture represented in at least sixtysix books that make up the Bible. When analyzing, and, mainly, observing the emergence of these two sovereigns in these two cultures on canvas, we perceive a figure that, even being presented as hyposufficient, is possibly the object most coveted by the gods, because, in the relationship between creator and creature, the faithfulness of the scale seems to be the adoration that generates obedience and harmony between the parties. Thus, it seems that the gods of the human race want to be remembered and to have their deeds told by the human being who, within this idealization of Man, created by the gods themselves and, often, similar to the creators, makes him the only living being capable of keep divine achievements alive and present. Based on the confrontation between the narratives studied here, we intend to understand points of contact and differentiation structured through the following themes: a) the cosmogonic narratives, that is, those related to the emergence and organization of the universe and things, b) the theogonic narratives, related to the engendering of divine beings, and c) the anthropogonic narratives, linked to the creation of humanity and, consequently, of man, woman and other non-human beings, but also non-animals, non-deities and with an anthropomorphic aspect (giants and demons).